Inflammatory responses in male soccer players following a single match and between consecutive matches: A systematic review - Duarte, W.; Paula, L. V.; Junior, J. L.; Goulart, K. N.; Chaves, S. F.; Pimenta, E. M. (International Journal of Sports Science & Coaching, 2025)
This systematic review investigated inflammatory responses in male soccer athletes (professionals and semi-professionals) following a single match and between consecutive matches. Searches were conducted for studies with available measurement data taken pre-match and subsequent other time points (post-match, 24 h, 48 h, and 72 h). The process was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) Protocols. Nineteen studies published from 2004 to 2023 were included. Interleukin 6 and White Blood Cells responses showed very large and moderate Effect Sizes (ES = 1.12) at post-match, respectively. Muscle soreness exhibited moderate ES at post-match and at 48 h (ES = 1.02), and large ES at 24 h (ES = 1.51). C-reactive protein (CRP) responses showed very large ES at 24 h and moderate at 48 h (ES = 0.86). Skin temperature of the lower limbs exhibited moderate and small ES at 24 h and 48 h (ES = 0.32), respectively. Following three consecutive matches (intervals = 4 days), only CRP exhibited significant effects between matches 2 and 3 compared to match 1 (ES = 0.57). These findings indicate increased inflammatory responses following a single match, and the 48-h window seems relevant, as at least two significant effects of these markers were reported at each time point within that period. Only CRP responses showed increasing effects in matches 2 and 3, thereby supporting the hypothesis of greater inflammatory magnitude following consecutive matches.